EISCAT_3D : EISCAT 3D Radar Receiver/Antenna Subsystem Report - Johansson, Jonny; Johansson, Gustav; Borg, Johan; Larsmark, Mikael; Lindgren, Tore (Luleå tekniska universitet, EISLAB, 2009)
Godkänd; 2009; 20091208 (ysko)